Pengaruh Kepuasan Kerja dan Motivasi terhadap Kinerja Karyawan pada PT. Astra International Tbk Daihatsu Banjarmasin - Sapar, Jhony Fahrin (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2022)
Job satisfaction is an emotional state that is pleasant or unpleasant for employees to view their work. Organizations that are not able to provide job satisfaction to their employees, will face the risk of productivity, increased turnover and high levels of employee absenteeism and allows increased work accidents, decreased physical and mental health of employees. Therefore, business organizations need to try to minimize the possibility of risk due to job dissatisfaction.The study tries to describe the actual situation regarding job satisfaction and motivation affect the performance of employees of PT. Astra International Tbk Daihatsu Banjarmasin.The research population is the entire subject to be studied. The subjects studied here are all employees of PT. Astra International Tbk Daihatsu Banjarmasin, totaling 80 (eighty) people. While the samples taken were 76 (seventy six) people.Employee job satisfaction affects performance while the factors that influence it are socially, physically and financially, the most influential factor is the financial factor because employees really hope that the company provides bonuses and incentives, the measurement of SPSS data processing uses a Likert scale to measure social factors , physical factors.